Kyai and the Phenomenon of Socio-Religious Patriarchy; Semantic Construct Analysis of the Meaning of Al-Rijāl and An-Nisā in the Qur'an - Milahtul Latifah (al-Afkar, Journal For Islamic Studies, 2024)
This research specifically aims to look at patriarchal systems and practices, whether intentional or not, that still exist in Islamic boarding schools. In a coherent manner, the author explains and dialogues things that are often indicated as having gender bias in Islamic boarding schools with social theory analysis, including, Islamic boarding schools' responses to women, women in the leadership system in Islamic boarding schools, gender bias in learning texts and masculinity norms in Islamic boarding schools. Daarul Mustaqiem Bogor. The aim of this research is to determine the influence of socio-religious understanding on the phenomenon of patriarchy in the Islamic boarding school leadership system. The social role of Kiai has a strong influence on the social aspects of Islamic boarding school education. There are several underlying points, namely: First, the issue of cultural values, a cultural problem that is still deeply rooted in many areas of society today is the strong ideology of patriarchy. In this context, Islamic education is a form of socio-religious (Islamic) education. Second, the strong patriarchal culture in the Islamic boarding school world cannot be separated from the dynamics of Islamic boarding school education. Thus, it cannot be separated from the domination of the figure of the Kyai who is known as the sole authority who holds the power of the Islamic Boarding School. It is hoped that this research can provide a related picture of a Kiai becoming an ideological symbol and the capital of deep religious knowledge which becomes a great capital for conquest and justification among society. Methods like this are then referred to in a social science perspective as hegemony. Such is the high position of a man (Kyai) in the social construct of Islamic boarding school education that Dhofier considers the most essential element of an Islamic boarding school. In this context, men (Kyai) have a central role in the world of Islamic boarding schools and have a big influence on the phenomenon of socio-religious patriarchy in Islamic boarding schools, providing comprehensive insight into extracting the meaning of Al-rijāl and al-Nisā in the Qur'an so that provides an objective meaning view of the true meaning in studying these terms through scientific semantic analysis of interpreters.